Mechanism of circRNA_4083 Circularization and Its Role in Regulating Cell Viability - Wenhao Li; Ting Yang; Haojie Wang; Hao Bai; Guobin Chang; Lingling Qiu (Animals)
Circular RNAs (circRNAs), a class of covalently closed non-coding RNAs, are pivotal regulators of gene expression and contributors to disease pathogenesis. This study elucidated the biogenesis, functional significance, and regulatory network of circRNA_4083, a novel exon-derived circRNA originating from exons 22 and 23 of the MSH3 gene in chicken. Through comprehensive molecular characterization—including Sanger sequencing, RNase R digestion assays, and subcellular localization—we confirmed the robust stability and predominant cytoplasmic localization of circRNA_4083 across diverse chicken tissues. Mechanistic investigations revealed that reverse complementary sequences within flanking intronic regions are indispensable for its circularization, as demonstrated by overexpression plasmids (#1–#4) in DF-1 cells. Functional analyses demonstrated that circRNA_4083 significantly inhibited cell apoptosis and increased cellular viability. Integrative bioinformatics approaches predicted a competing endogenous RNA (ceRNA) network comprising 12 miRNAs and 2132 target genes (FDR < 0.05), with significant enrichment in pathways critical to genomic stability, including non-homologous end joining (NHEJ) and ubiquitin-mediated proteolysis. These findings position circRNA_4083 as a key modulator of cellular viability and genomic integrity, with potential implications for avian leukosis virus-J (ALV-J) pathogenesis and resistance breeding strategies. This work advances our understanding of circRNA-driven regulatory mechanisms in avian species and underscores their relevance in poultry health.